PM2.5 exposure in utero contributes to neonatal cardiac dysfunction in mice. (November 2017) - Tanwar, Vineeta; Adelstein, Jeremy M.; Grimmer, Jacob A.; Youtz, Dane J.; Sugar, Benjamin P.; Wold, Loren E.
Abstract: Objective: Exposure of fine particulate matter (PM2.5 ) to pregnant dams has been shown to be strongly associated with adverse cardiovascular outcomes in offspring at adulthood, however, effects evident during neonatal periods are unclear. We designed this study to examine cardiac function of neonatal mice (14 days old) exposed to in utero PM2.5 . Methods: Pregnant FVB female mice were exposed either to filtered air (FA) or PM2.5 at an average concentration of 91.78 μg/m 3 for 6 h/day, 5 days/wk (similar to exposure in a large industrial area) throughout the gestation period (21 days). After birth, animals were analyzed at day 14 of life. Results: Fourteen day old mice exposed to PM2.5 during the in utero period demonstrated decreased fractional shortening (%FS, 41.1 ± 1.2% FA, 33.7 ± 1.2% PM2.5, p < 0.01) and LVEDd (2.87 ± 0.08 mm FA, 2.58 ± 0.07 mm PM2.5, p < 0.05) compared to FA exposed mice. Contractile kinetics and calcium transients in isolated cardiomyocytes from PM2.5 exposed mice illustrated reduced peak shortening (%PS, 16.7 ± 0.5% FA, 14.7 ± 0.4% PM2.5, p < 0.01), negative contractile velocity (-dL/dT, −6.91 ± 0.3 μm/s FA, −5.46 ± 0.2 μm/s PM2.5, p < 0.001), increased time to relaxation 90% (TR90, 0.07 ± 0.003 s FA, 0.08 ± 0.004 s PM2.5, p < 0.05), decreased calcium transient amplitude (Δ340/380, 33.8 ± 3.4 FA, 29.5 ± 2.8 p.m.2.5 ) and slower fluorescence decay rate (τ, 0.72 ± 0.1 s FA, 1.16 ± 0.15 s PM2.5, p < 0.05). Immunoblotting studies demonstrated alterations in expression of Ca 2+ handling proteins- SERCA-2A, p-PLN, NCX and CaV 1.2 in hearts of 14 day old in utero PM2.5 exposed mice compared to FA exposed hearts. Conclusion: PM2.5 exposure during the critical in utero period adversely affects the developing mouse fetus leading to functional cardiac changes that were evident during the very early (14 days) stages of adolescence. These data demonstrated that exposure to PM2.5 during the gestation period significantly impacts cardiovascular outcomes early in life. Graphical abstract: Highlights: PM2.5 exposure during the in utero period exerts harmful effects on the developing fetus. This study is the first to examine effects of in utero PM2.5 exposure on neonatal mice. Exposure to in utero PM2.5 leads to neonatal cardiac dysfunction. In utero PM2.5 exposure alters Ca 2+ handling protein expression leading to functional impairments.